Potentials of Streptomyces rochei ERY1 as an Endophytic Actinobacterium Inhibiting Damping-off Pathogenic Fungi and Growth Promoting of Cabbage Seedling - Prapaipit Suwitchayanon (Science Faculty of Chiang Mai University, 2019)
Streptomyces rochei ERY1, an endophytic actinobacterium isolated from Eryngium foetidum L., was investigated for a production of antifungal metabolites against Pythium aphanidermatum and Sclerotium rolfsii and a growth promoter in Chinese cabbage seedling. An antifungal metabolite secreted by S. rochei ERY1 inhibited the mycelial growth of P. aphanidermatum and S. rolfsii by 84.31% and 62.34%, respectively, and also inhibited a reproduction of P. aphanidermatum. IAA, GA3 and cytokinin in the culture filtrate of S. rochei ERY1 were detected by HPLC as 4.49 mg/l, 0.18 mg/l and 0.07 mg/l, respectively, which implied that S. rochei ERY1 could significantly increase fresh weight and dry weight of Chinese cabbage seedling. In vitro colonization trials of Chinese cabbage were clearly proved by SEM as mycelial development of S. rochei ERY1 bulging beneath epicuticular wax layer, producing aerial spores and germinating spore on surface of the tested explants. This is the initial report which demonstrated colonization of S. rochei in Chinese cabbage. In addition, re-isolation percentage of the inoculated Chinese cabbage revealed that the colonization of S. rochei ERY1 was seedling explant-dependent. The present results suggest that S. rochei ERY1 has high potentials to be developed as a biological control product for an alternative disease management option in the future.